A new impact assessment model to integrate space debris within the life cycle assessment-based environmental footprint of space systems - Maury-Micolier, Thibaut; Maury-Micolier, Alice; Helias, Arnaud; Sonnemann, Guido; Loubet, Philippe (Frontiers in Space Technologies, 2022)
The United Nations’ treaties consider outer space as a ‘Global Common’ of humankind such as oceans, the atmosphere, or the Antarctic. By analogy to conventional environmental impacts, the potential release of debris or generation of fragments can be considered as the emission of an environmental stressor damaging the orbital ‘natural’ resource which supports space activities. Hence, it appears relevant to integrate systematically the impact of the emission of debris on the orbital resource within the life cycle impact assessment (LCIA) step to broaden the scope of life cycle assessment (LCA) for space systems. The main objective of this article is to propose a set of characterization factors to compute the impact caused by the generation of debris within the orbital environment. To do so, the proposed approach follows the methodology of emission-related characterization models in LCIA. the characterization model enables to link the emission of debris and final economic damages to space activities through a complete impact pathway including the fate of debris in downstream orbital compartments, the exposure of targeted space objects to this debris, and the economic damage in case of collision between the debris and the space object. The model is computed for different compartments of the low earth orbit (LEO) region thanks to a discretization of the orbital environment. Results show that the potential damages are the highest for orbital compartments located in the orbital bands of altitude/inclination: 550-2000km/52-54°, 1200-2000km/86-88°, 400-2000km/96-100°, because of the downstream location of Starlink constellation, OneWeb constellation, and earth observation satellites, respectively. The proposed set of CFs can be used in the LCA of different space systems in order to include impacts and damages related to space debris, along with other environmental impacts. This original development fully in line with the standardized LCIA framework would have potential for further integration into harmonised sector-specific rules for the European space sector such as product environmental footprint category rules (PEFCRs).